Editorial - Turton, Rai; Hayes, Grahame (PINS-Psychology in Society, 2025)
Kant claimed to have been awakened from his dogmatic slumber by the writings of Hume. Some philosophy students have been heard to joke that the outcome of his awakening was the even more profound slumber of the "Transcendental Anaesthetic". Perhaps what this feeble jest indicates is that awakening is an uncertain process. In the course of its first eleven issues, PINS has delivered some pricks to the sleeping mass which have (hopefully) contributed to the stirrings we have seen during the past few years. It is essential that we continue to do this as a vital element of our efforts to promote relevant psychological practices in South Africa. One of the most powerful instruments in this task is the Uncomfortable Question which, if correctly posed, becomes an irritant to the sleepers. The articles, debates and reviews published in our first eleven issues have posed many, and we hope that these in our twelfth continue to do the same, lest the snoring becomes loud and deep once more.